2016
DOI: 10.1136/jmedgenet-2015-103529
|View full text |Cite
|
Sign up to set email alerts
|

No evidence that protein truncating variants inBRIP1are associated with breast cancer risk: implications for gene panel testing

Abstract: Background BRCA1 interacting protein C-terminal helicase 1 (BRIP1) is one of the Fanconi Anaemia Complementation (FANC) group family of DNA repair proteins. Biallelic mutations in BRIP1 are responsible for FANC group J, and previous studies have also suggested that rare protein truncating variants in BRIP1 are associated with an increased risk of breast cancer. These studies have led to inclusion of BRIP1 on targeted sequencing panels for breast cancer risk prediction. Methods We evaluated a truncating varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
77
3
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 43 publications
7
77
3
6
Order By: Relevance
“…The researchers concluded that clear evidence of an association with an increased risk of breast cancer (clinical validity) was available for variants of PALB2 , ATM , CHEK2 , and NBN (based on several descriptions of a single founder mutation), and for a clinical diagnosis of neurofibromatosis type 1. The authors did not find conclusive evidence of an association between increased breast-cancer risk and mutations in other genes (such as RAD50 , BARD1 , XRCC2 , and MRE11A ), and noted that studies have failed to demonstrate reproducible associations between an elevated breast-cancer risk and mutations in BRIP1 or RAD51C/D 2023 . Investigators have published isolated reports of similar associations for a number of variants in other genes (such as MEN1 , RECQ , and RINT1 ) 2426 , but these results await confirmation in additional studies, preferably of a large size.…”
Section: Gene Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers concluded that clear evidence of an association with an increased risk of breast cancer (clinical validity) was available for variants of PALB2 , ATM , CHEK2 , and NBN (based on several descriptions of a single founder mutation), and for a clinical diagnosis of neurofibromatosis type 1. The authors did not find conclusive evidence of an association between increased breast-cancer risk and mutations in other genes (such as RAD50 , BARD1 , XRCC2 , and MRE11A ), and noted that studies have failed to demonstrate reproducible associations between an elevated breast-cancer risk and mutations in BRIP1 or RAD51C/D 2023 . Investigators have published isolated reports of similar associations for a number of variants in other genes (such as MEN1 , RECQ , and RINT1 ) 2426 , but these results await confirmation in additional studies, preferably of a large size.…”
Section: Gene Selectionmentioning
confidence: 99%
“…Average relative-risk multipliers were derived from the systematic review of Easton and colleagues 20 , for breast cancer risk, and from the recently published population-based case–control studies of Ramus et al . 27 and Song et al .…”
Section: Age-specific and Lifetime Risksmentioning
confidence: 99%
“…A case in point is BRIP1 , which was first reported to be associated with breast cancer in 2006, 7 an observation that was not substantiated by a much larger study published ten years later. 8 Yet this gene is still found on many commercially available hereditary breast cancer panels. 1 In contrast, screening for single nucleotide polymorphisms is not typically included in panel tests, although it has been estimated that they can cumulatively confer a risk of 29% (by age 80 years for women in the top 1% for polygenic risk score 4 ) which is comparable to moderate risk susceptibility genes (30% and 28% for CHEK2 and ATM , respectively 9 ).…”
Section: Availability and Testing Criteriamentioning
confidence: 99%
“…In conclusion, based on data from this4 and previous studies,11–13 BRIP1 should be considered an ovarian cancer susceptibility gene but not a breast cancer susceptibility gene. This has important implications for individuals undergoing genetic testing for hereditary breast cancer and/or ovarian cancer.…”
mentioning
confidence: 55%
“…In this issue of JMG , Easton and colleagues,4 using a very large series of cases and controls, report a failure to replicate the association3 between BRIP1 truncating mutations and breast cancer risk. Here, the authors first genotyped the recurrent BRIP1 truncating mutation c.2392C>T (p.Arg798Ter) in more than 48 000 breast cancer cases and 43 000 controls and then sequenced the entire coding region of BRIP1 in more than 16 000 cases and 8000 controls.…”
mentioning
confidence: 99%